Simulation of SNG Production Through Catalytic Gasification of Biomass - Farag, Ebtehal Eisa Ragheb Eisa (Universiti Teknologi PETRONAS, 2014)
With the increasing demand for clean and renewable sources of energy, different kinds of biomass and agricultural wastes have become the focus of research especially in agriculture rich countries like Malaysia, Indonesia, and Thailand. The oil palm is an agro-industrial commodity that is used extensively in the fore mentioned countries to produce edible oil. The residual branches of oil palm fruit tree are a natural and unavoidable by-product of this industry. This paper provides the basic modelling of thermo-chemical energy transformation of residual waste from the oil palm fruit tree to chemical energy using high temperature steam gasification. The final product of this process is pure synthetic natural gas. In the second stage of this project, the operational parameters of the process were investigated and analyzed to develop an operationally optimum model. The modelling was performed based on data extracted from multiple research papers (stated in text and references), and simulated using AspenTech. HYSYS Version 8.0.